Knowledge and Attitude of Biology Teacher Candidate Students towards Genetically Modified Organisms (GMOs) - Purwanti Pratiwi Purbosari; Destri Ratna Ma'rifah (Tadris Biologi Fakultas Ilmu Tarbiyah dan Keguruan IAIN SYEKH NURJATI CIREBON, 2021)
Genetically Modified Organisms (GMOs) provide many benefits and promote public debate regarding their safety and risks. Currently, there is a lack of research that specifically focuses on biology teacher candidates’ knowledge and attitude towards GMOs. This study aimed to explore the knowledge and attitude of biology teacher candidate students towards GMOs. The data was collected through an online questionnaire distributed. The data scores of knowledge and attitude were analyzed using an independent sample t-test to analyze the effect of the genetic course on the knowledge and attitude of biology teacher candidate students towards GMOs. A Pearson correlation was used to determine the correlation between teacher candidates' knowledge and attitudes towards GMOs. As a result, genetic courses do not significantly affect the knowledge or attitude of biology teacher candidate students towards GMOs. There was a positive correlation between knowledge and attitude of biology teacher candidate students towards GMOs.